2016
DOI: 10.1098/rsbl.2015.0708
|View full text |Cite
|
Sign up to set email alerts
|

Individual variation in whole-animal hypoxia tolerance is associated with cardiac hypoxia tolerance in a marine teleost

Abstract: Hypoxia is a pervasive problem in coastal environments and is predicted to have enduring impacts on aquatic ecosystems. Intraspecific variation in hypoxia tolerance is well documented in fish; however, the factors underlying this variation remain unknown. Here, we investigate the role of the heart in individual hypoxia tolerance of the European sea bass (Dicentrarchus labrax). We found individual whole-animal hypoxia tolerance is a stable trait in sea bass for more than 18 months (duration of study). We next e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…In the open ocean, fish often experience cold, hypoxic conditions during oscillatory dives which approach or extend beyond the depths at which the mixed layer ends and the oxygen minimum zone begins (Bernal et al., ). Segregation of vertical habitat use of open ocean fishes is driven by the physiological ability of species to maintain sufficient cardiorespiratory capacity for active behaviours under these challenging conditions (Bernal et al., , ), a trait governed by a suite of physiological factors which are known to show interindividual variation (Joyce et al., ; Ollivier, Marchant, Le Bayon, Servili, & Claireaux, ; Ozolina, Shiels, Ollivier, & Claireaux, ). This variation may ultimately manifest as differences in the maximum depth attainable by individual fish, or the amount of time fish spend at a given depth, and so give rise to intraspecific differences in vertical habitat use (Cosgrove, Arregui, Arrizabalaga, Goni, & Sheridan, ; Quayle, Righton, Hetherington, & Pickett, ; Vaudo et al., ), with implications for whether individuals are available to gears deployed at specific depths (Olsen, Heupel, Simpfendorfer, & Moland, ).…”
Section: The Capture Process and Selection On Physiological Traitsmentioning
confidence: 99%
“…In the open ocean, fish often experience cold, hypoxic conditions during oscillatory dives which approach or extend beyond the depths at which the mixed layer ends and the oxygen minimum zone begins (Bernal et al., ). Segregation of vertical habitat use of open ocean fishes is driven by the physiological ability of species to maintain sufficient cardiorespiratory capacity for active behaviours under these challenging conditions (Bernal et al., , ), a trait governed by a suite of physiological factors which are known to show interindividual variation (Joyce et al., ; Ollivier, Marchant, Le Bayon, Servili, & Claireaux, ; Ozolina, Shiels, Ollivier, & Claireaux, ). This variation may ultimately manifest as differences in the maximum depth attainable by individual fish, or the amount of time fish spend at a given depth, and so give rise to intraspecific differences in vertical habitat use (Cosgrove, Arregui, Arrizabalaga, Goni, & Sheridan, ; Quayle, Righton, Hetherington, & Pickett, ; Vaudo et al., ), with implications for whether individuals are available to gears deployed at specific depths (Olsen, Heupel, Simpfendorfer, & Moland, ).…”
Section: The Capture Process and Selection On Physiological Traitsmentioning
confidence: 99%
“…(2012a) found that in juvenile European seabass, the tendency to take risks showed low repeatability across a gradient of oxygen availabilities ( R and Spearman's ρ), probably because variation in spontaneous swimming activity was affected by the tendency of some individuals to perform aquatic surface respiration in hypoxic conditions. Joyce et al . (2016) examined the long term repeatability (18 months) of hypoxia tolerance in the European seabass and found that variability in whole-animal hypoxia tolerance was explained by interindividual variance in cardiac hypoxia tolerance.…”
Section: Environmental Contexts Affecting Trait Variation and Repeatamentioning
confidence: 99%
“…The variation among individuals was not explained by euthanasia method, body mass, ending DO, temperature or water osmolarity, nor were these correlations observed for fish held under normoxia. It is tempting to speculate that this variation is related to difference in hypoxia tolerance among individuals, a subject that has received considerable recent attention (Clarieaux et al ., ; Roze et al ., ; Claireaux & Chabot, ; Ejbye‐Ernst et al ., ; Joyce et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The variation among individuals was not explained by euthanasia method, body mass, ending DO, temperature or water osmolarity, nor were these correlations observed for fish held under normoxia. It is tempting to speculate that this variation is related to difference in hypoxia tolerance among individuals, a subject that has received considerable recent attention (Clarieaux et al, 2013;Roze et al, 2013;Claireaux & Chabot, 2016;Ejbye-Ernst et al, 2016;Joyce et al, 2016). Twenty-four hour exposure of F. grandis to hypoxia also caused fish to reach LOE sooner than normoxic controls, presumably due to the accumulation of stress during hypoxia pre-disposing fish to succumb faster to the effects of euthanizing agents.…”
Section: E F F E C T S O F H Y P Ox I Amentioning
confidence: 99%